2012
DOI: 10.1007/s00431-012-1913-3
|View full text |Cite
|
Sign up to set email alerts
|

Cyclosporine versus mycophenolate mofetil for maintenance of remission of steroid-dependent nephrotic syndrome after a single infusion of rituximab

Abstract: In patients with severe steroid-dependent NS, CsA appears to be more effective than MMF for maintaining remission after a single infusion of RTX.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
23
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
6
4

Relationship

0
10

Authors

Journals

citations
Cited by 39 publications
(23 citation statements)
references
References 20 publications
0
23
0
Order By: Relevance
“…A therapeutic window for MPA AUC 12 in autoimmune disease patients has not been established yet and it is not clear whether or how MPA C trough in people with autoimmune disease relate to MPA exposure (Abd Rahman et al, 2014). To our knowledge, for children with nephrotic syndrome there are still not many studies concerning target MPA pharmacokinetic parameters, associated with obtaining a remission of the disease (Fujinaga et al, 2013;Gellermann et al, 2013). Therefore, in children included in the study, we focused mainly on MPA C trough and AUC 12 values and their relation to the efficacy of MMF treatment.…”
Section: Discussionmentioning
confidence: 95%
“…A therapeutic window for MPA AUC 12 in autoimmune disease patients has not been established yet and it is not clear whether or how MPA C trough in people with autoimmune disease relate to MPA exposure (Abd Rahman et al, 2014). To our knowledge, for children with nephrotic syndrome there are still not many studies concerning target MPA pharmacokinetic parameters, associated with obtaining a remission of the disease (Fujinaga et al, 2013;Gellermann et al, 2013). Therefore, in children included in the study, we focused mainly on MPA C trough and AUC 12 values and their relation to the efficacy of MMF treatment.…”
Section: Discussionmentioning
confidence: 95%
“…A Japanese group [ 18 ] reported that maintenance therapy with MMF can help avoid the repeated use of RTX and may contribute to its safer use, as well as to fewer serious RTX-associated adverse events. In contrast, another Japanese group [ 19 ] compared cyclosporine with MMF for maintenance of SDNS remission after a single infusion of RTX and found that cyclosporine appeared to be more effective than MMF. In our study, CNI was used only in cases of relapse, and no patients received MMF at the time of initial RTX treatment or thereafter.…”
Section: Discussionmentioning
confidence: 99%
“…Low-quality evidence supports the use of alkylating agents such as cyclophosphamide in SDNS and FRNS podocytopathies to reduce the cumulative dose of steroids 146 but these regimens have been progressively abandoned in developed countries owing to their unfavourable safety profile (TABlE 2). In paediatric patients, mycophenolate mofetil seems equally as effective as levamisole 189 but not as effective as ciclosporin in achieving remission [190][191][192] , although the evidence is still limited 157 . In addition, higher doses of mycophenolate mofetil than those used in kidney-transplanted recipients seem to be necessary in children with nephrotic syndrome to achieve remission 192 .…”
Section: Sdns and Frnsmentioning
confidence: 99%